COMPOUND HETEROZYGOTE REASON FOR JUVENILE FORM OF TAY-SACHIS DISEASE -CASE REPORT - Nonkulovski, Danilo; Duma, Filip; Dicoska, Mateja; Kirovski, Ilija; Maneva Kuzeska, Konstandina; Muaremoska-Kanzoska, Lejla (Journal of Morphological Sciences, 2022)
Tay-Sachs diseases are group of rare autosomal recessive lysosomal disorders, GM2-gangliozidoses. They are progressive neurodegenerative diseases, caused by a mutation in the enzyme Î²-hexosaminidase A. Depending on the time of presentation of symptoms, there are three forms: infantile, juvenile and adult. We present a 8 year old patient, who is presented at the age of 4 with progressive deterioration in psychomotor and speech skills, pyramidal symptoms, ataxia and muscle weakness. The EEG showed bihemispheric fast spike waves and the MRI showed no findings of organic disease. Finally a molecular genetic testing was made, which proved the diagnosis of juvenile form of Tay-Sachs disease. It was determined that the patient is a compound heterozygote, with two different mutations in the alleles of the HEXA gene, one  inherited from the mother and the other one from the father. The juvenile Tay-Sachs disease is characterized with beginnig between the age of 2 to 10 years old. Clinically it is presented with muscle weakness, incoordination, ataxia, dysarthria, dysphagia and progressive spasticity. It progresses to development of dementia, convulsions, blindness and vegetative state with decerebrate rigidity and death by the age of 15. It is inherited autosomal recessive with one mutation present on both alleles of the HEXA gene. Treatment options for Tay-Sachs disease currently are only symptomatic and supportive. There are ongoing researches for curative treatments for Tay-Sachs, like enzyme replacement, chaperone, substrate reduction and gene therapy. Keywords : Tay-Sachs disease, juvenile form, compound heterozygote.